PERSONNEL MANAGER LEADERSHIP ROLE IN IMPROVING EMPLOYEE PERFORMANCE - Manafe, Leonard Adrie (FEB - Universitas Lampung, 2022)
The purpose of this study is to determine the personnel manager leadership role in improving employee performance at PT. Arto Manunggal Surabaya City (AM) and to find out the obstacles and how to overcome them. The approach used in this study is a descriptive approach using qualitative methods. Data collection techniques in this study are observation, interviews, and documentation. Research informants were selected by purpose sampling where the informants were taken as each division representatives. The results showed that personnel manager had carried out the function of a leader role through interpersonal roles, informational roles and decision-making roles in improving employee performance in AM companies.